Elements of Financial Risk Management, 2nd Edition - Christoffersen, Peter; O'Reilly for Higher Education (Firm); Ohio Library and Information Network (Academic Press, Amsterdam, 2011)
The Second Edition of this best-selling book expands its advanced approach to financial risk models by covering market, credit, and integrated risk. With new data that cover the recent financial crisis, it combines Excel-based empirical exercises at the end of each chapter with online exercises so readers can use their own data. Its unified GARCH modeling approach, empirically sophisticated and relevant yet easy to implement, sets this book apart from others. Five new chapters and updated end-of-chapter questions and exercises, as well as Excel-solutions manual, support its step-by-step approach to choosing tools and solving problems. Examines market risk, credit risk, and operational risk Provides exceptional coverage of GARCH models Features online Excel-based empirical exercises
Made available through: Safari, an O'Reilly Media Company
Keywords: Risk management